083 Discharged from paediatric intensive care unit (PICU): a mixed – methods study of young people's (YP) anxiety levels and experiences after PICU discharge. (December 2018) - Bichard, E; Wray, J; Cooper, J; Aitken, L
Abstract : Introduction: Young People (YP) aged 13–18 years admitted to Paediatric Intensive Care (PICU), experience physical and psychological challenges during their recovery. YP likely have different experiences than children or adults (Manning et al, 2017). Anxiety as a characteristic of illness recovery is largely under-reported, as are the experiences of YP of this age range. This study measured the levels of anxiety that YP experience and explored the experiences of YP after PICU discharge. Design mixed methods: explanatory sequential design. Demographic data in addition to the Paediatric Index of Mortality Score (PIMS 2) will be collected. Quantitative component: Hospital Anxiety and Depression Score, anxiety subscale only (HADS-A) will be collected at 48–96 hours and at 4 weeks after PICU discharge. Qualitative component: Semi-structured interviews based on a cross-section of participants with a range of HADS-A scores. Results: Preliminary results demonstrate that HADS-A scores are generally low in contrast to descriptions of anxiety-provoking events and experiences on PICU, elicited during interviews. HADS-A scores were mean=8.4 (n=18) 48 hours post PICU discharge. Mean score of 8.9 is classified as mild anxiety using the HADS-A subscale. On average these scores had reduced to Mean=5.5 (n=9) 4 weeks later which suggests that no anxiety is present (Zigmund and Snaith 1983). The Qualitative themes emerging relate to staff and family presence and the YP's experiences of pharmaceuticals, medical and nursing interventions Conclusion: The anxiety scores do not reflect the experiences described by YP during interview; this raises questions about the context of experiences and the multifactorial psychological impact of a PICU admission.